Evaluation of Lifting Techniques Using Optoelectronic Systems with Knee Range of Motion Restrictions - Storari, Lorenzo; Barbari, Valerio; Maselli, Filippo; Nardello, Francesca; Zamparo, Paola; Scafoglieri, Aldo; Cattrysse, Erik (International Journal of Sports Medicine, 2025)
This study explored the effect of knee range of motion (ROM) restrictions on lumbar spine kinematics and posterior chain muscle activity during squat and stoop lifting tasks. This relationship reflects the concept of regional interdependence, where impairments in one anatomical area may influence others, a key principle in the kinetic chain approach. Fifteen healthy adults performed squat and stoop lifting tasks under three knee ROM conditions (squat: free/0–60°/0–90°; stoop: free/0°/0–30°) using optoelectronic motion capture and electromyographic (EMG) systems. One-way analysis of variance was applied to analyze lumbar spine angles in flexion/extension, side bending, and rotation and to assess muscle activation patterns for five posterior chain muscles. No significant effects of knee ROM restrictions were observed for lumbar flexion/extension or side bending (p>0.15), but pelvic rotation differed significantly (p=0.0103). EMG analysis showed increased activation of the Gastrocnemius Lateralis and Biceps Femoris (p<0.001), while Gluteus Maximus and Latissimus Dorsi activation remained unchanged. Knee ROM restrictions influenced EMG muscle activation in distal posterior chain muscles and altered pelvic rotation, suggesting localized compensatory mechanisms. Results highlight the variation in muscle activation patterns and kinetic adjustments during squat and stoop lifting tasks in healthy individuals simulating knee ROM deficits, osteoarthritis, or low back pain conditions.
Keywords: lumbar vertebrae; biomechanical phenomena; knee joint; lifting; exercise movement techniques